The coaching black box: Risk mitigation during change management - William Percy; Kevin Dow (Journal of Risk and Financial Management, 2021)
A case study of strategic renewal in the Chinese education market, this paper explores a non-directive coaching model and its impact on risk mitigation, knowledge exchange and innovation in strategic renewal through the application of multi-tiered coaching and manager coaches. Through an ethnographic action research methodology, we ask "Can coaching mitigate organisational risk and increase the likelihood of positive outcomes in change management?" and "Can managers, acting as internal coaches, increase knowledge socialisation and mitigate risk in the change management process?" The paper finds that there is no inherent failure rate in the change management process and that a strategic management approach can mitigate risk liberating managers and organisations to seek to create the collaborative environments that support organisational learning and strategic renewal, thus moving beyond a narrative of failure to one of strategic empowerment and a strategic management approach to risk mitigation. We conclude that a data-driven approach to organisational learning and Professional Learning Communities helps teams to ask the right questions and to mitigate risk through better aligning the organisation to its strategic reality, exploiting organisational learning to achieve competitive advantage and ensuring that systems and processes continue to match the emerging strategic reality.
Keywords: 330; change management; coaching; innovation; knowledge management; knowledge socialisation; manager coach; people analytics; risk mitigation; strategic renewal; team coaching